Good bad girl - Feeney, Alice (Flatiron Books, 2023)
"Sometimes bad things happen to good people, so good people have to do bad things. Our Queen of Twists, bestselling author of Daisy Darker and Rock Paper Scissors Alice Feeney, returns with another thrilling mystery filled with drama and her trademark surprises. Twenty years after a baby is stolen from a stroller, a woman is murdered in a care home. The two crimes are somehow linked, and a good bad girl may be the key to discovering the truth. Edith may have been tricked into a nursing home, but at eighty-years-young, she's planning her escape. Patience works there, cleaning messes and bonding with Edith, a kindred spirit. But Patience is lying to Edith about almost everything. Edith's own daughter, Clio, won't speak to her. And someone new is about to knock on Clio's door...and their intentions aren't good. With every reason to distrust each other, the women must solve a mystery with three suspects, two murders, and one victim. If they do, they might just find out what happened to the baby who disappeared, the mother who lost her, and the connections that bind them. In the style of Daisy Darker and Rock Paper Scissors, Good Bad Girl is a thriller in which nobody can be trusted and the twists come fast and furious"--